HIV Pre-Exposure Prophylaxis Cascade Stages Among Men Who Have Sex With Men With Sexually Transmitted Infections in China: Multicenter Cross-Sectional Survey Study - Xue Yang; Wenting Kang; Zhuoer Zhang; Houlin Tang; Dapeng Zhang; Lijun Sun; Zaicun Li; An Liu (JMIR Public Health and Surveillance)
Abstract BackgroundThere is limited literature available regarding the knowledge and use of HIV pre-exposure prophylaxis (PrEP) among men who have sex with men (MSM) with sexually transmitted infections (STIs). ObjectiveThis study’s objective was to explore the HIV PrEP cascade stages (knowledge, willingness to use, and use) among MSM with STIs in China, in order to promote the implementation of PrEP in this population. MethodsA cross-sectional study was conducted using a respondent-driven sampling method in 19 cities in China, from January to August 2022. The study collected data on demographics, behaviors, and PrEP cascade stages from participants who were not infected with HIV and who self-reported being recently infected with STIs. After using ResultsBy August 2022, following screening and exclusion, a total of 1329 MSM were included in the study. Among them, 85.55% (n=1137) had heard of PrEP, 81.57% (n=1084) expressed their willingness to use PrEP if engaging in high-risk HIV behaviors, 70.58% (n=938) had consulted a health care professional about PrEP, 62.98% (n=837) reported having used PrEP, and 46.35% (n=616) possessed a basic understanding of PrEP. The results of multivariate logistic regression analyses showed that the same factors significantly influenced both knowledge of PrEP and willingness to take PrEP, including age, education, marital status, income, condom usage, participation in group sex, HIV status of the most recent male sexual partner, and postexposure prophylaxis (PEP) usage. The factors significantly related to the PrEP use included income, engagement in commercial sex, participation in group sex, HIV status of the most recent male sexual partner, new drug usage, and PEP usage. ConclusionsMSM with STIs were engaged with the PrEP cascade stages at a relatively high rate, but they lacked an understanding of PrEP and underestimated HIV risk. The prevalence of having a basic understanding of PrEP was lower than PrEP usage, and this suboptimal awareness could impede PrEP efficacy and lead to risk compensation.